Pengaruh Konsentrasi Biourin Kelinci Terhadap Pertumbuhan Vegetatif Bayam Batik (Amaranthus Tricolor L. var. Giti Merah) - Rafdinal, Sy. Hasan Agil Riza Linda (Jurnal Protobiont, 2019)
Batik spinach (Amaranthus tricolor L.) is a plant that is rich in nutrients and can be used as diabetes medicine and dysentery. Therefore, increasing the growth of batik spinach plants needs to be done, one of which is the use of organic fertilizers, which can be used as rabbit biourin. The use of rabbit urine is done because rabbit urine has a high nutrient content compared to other livestock. The aim of the study was to determine the effect of biourin on the growth of batik spinach (Amaranthus tricolor L.). The study used a Completely Randomized Design (CRD) with 5 levels of concentration treatment consisting of controls, 25 ml / L, 30 ml / L, 35 ml / L, 40 ml / L, with 5 replications. The results showed that the administration of rabbit biourin significantly affected plant height, number of leaves, wet weight, dry weight and ratio of roots / canopy. The concentration of 25 ml / L gave the highest effect on the parameters of plant height, leaf number, root / crown ratio, wet weight, and dry weight.